Subarachnoid haemorrhage mimicking transient ST-segment elevation myocardial infarction. Issue 4 (August 2015) - Lai, C.-H.; Juan, Y.-H.; Chang, S.-L.; Lee, W.-L.; How, C.-K.; Hsu, T.-F.
<x content-type="archive" xml:space="preserve">Abstract</x> Patients often present to the emergency department with loss of consciousness. The differential diagnosis of such condition may be difficult because of limited clinical information. The authors present a case of subarachnoid haemorrhage (SAH) with initial electrocardiographic (ECG) finding mimicking ST-segment elevation myocardial infarction (STEMI), which was confirmed to resolve in a follow-up study. Accurate and timely diagnosis of SAH-related ST-segment elevation was important, as the therapeutic strategy for SAH is completely different from that for STEMI. If the clinicians do not have other tools for diagnosis, the follow-up ECG may help us make a most possible diagnosis.